2003
DOI: 10.1021/ja034162h
|View full text |Cite
|
Sign up to set email alerts
|

Mithramycin SK, A Novel Antitumor Drug with Improved Therapeutic Index, Mithramycin SA, and Demycarosyl-mithramycin SK:  Three New Products Generated in the Mithramycin Producer Streptomyces argillaceus through Combinatorial Biosynthesis

Abstract: To gain initial structure-activity relationships regarding the highly functionalized pentyl side chain attached at C-3 of mithramycin (MTM), we focused on a post-polyketide synthase (post-PKS) tailoring step of the MTM biosynthesis by Streptomyces argillaceus ATCC 12956, which was proposed to be catalyzed by ketoreductase (KR) MtmW. In this last step of the MTM biosynthesis, a keto group of the pentyl side chain is reduced to a secondary alcohol, and we anticipated the generation of an MTM derivative with an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
155
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 121 publications
(160 citation statements)
references
References 43 publications
4
155
0
1
Order By: Relevance
“…[9][10][11][12][13] In order to address these issues, extensive combinatorial biosynthesis has been performed on the MTM pathway and has resulted in several novel analogs. [14][15][16] The present authors have shown that the inactivation of the mtmW gene, which codes for the last enzyme in the MTM biosynthetic pathway, yields the most favorable of the new analogs, MTM SK (SK) and MTMSDK (SDK). 15,16 Both SK and SDK exhibited higher anticancer activity than the native MTM, 15,16 yet their short plasma retention time and low accumulation in tumors remained to be improved.…”
Section: Introductionmentioning
confidence: 91%
“…[9][10][11][12][13] In order to address these issues, extensive combinatorial biosynthesis has been performed on the MTM pathway and has resulted in several novel analogs. [14][15][16] The present authors have shown that the inactivation of the mtmW gene, which codes for the last enzyme in the MTM biosynthetic pathway, yields the most favorable of the new analogs, MTM SK (SK) and MTMSDK (SDK). 15,16 Both SK and SDK exhibited higher anticancer activity than the native MTM, 15,16 yet their short plasma retention time and low accumulation in tumors remained to be improved.…”
Section: Introductionmentioning
confidence: 91%
“…Mithramycin A is an anti-tumour antibiotic which inhibits transcription from promoters containing GC-rich DNA sequences (Miller et al, 1987;Blume et al, 1991). Mithramycin A is licensed for clinical use, and therefore the elucidation of its mechanisms of action is of interest in that respect (Remsing et al, 2003;Ferrante et al, 2004). In this report, however, we have focussed on its application as a useful tool to probe the mechanisms whereby the expression of Hdm2 is regulated in cancer cells.…”
Section: Regulation Of Hdm2 By Mithramycin a A Phillips Et Almentioning
confidence: 99%
“…We next analysed the capabilities of siPa and siE1 to modulate sensitivity of MDA-MB-231 cells to the antitumor drug mithramycin A (Remsing et al, 2003) and UV light. Both PKCa and Ets1 have been reported to be involved in stress-induced responses.…”
Section: Sipa Interferes With Ets1 Protein Synthesis and Stabilitymentioning
confidence: 99%